Pengembangan Media Pembelajaran SNAMBO (Snake Math Box) Materi KPK dan FPB Kelas IV SDN Pomahan I - Sholikah, Siti Amirotus; Maghfiroh, Lailatul (AJER: Advanced Journal of Education and Religion, 2025)
This study aims to analyze the development, validity, effectiveness, and students’ responses to the SNAMBO learning media in improving fourth grade students’ understanding of Least Common Multiple (LCM) and Greatest Common Divisor (GCD) at SDN Pomahan I. The research applied the Research and Development (R&D) method using the ADDIE model, which included expert validation, small-group and large-group trials, as well as student response questionnaires. The results of material validation obtained a score of 89% with a very feasible category, while media validation achieved 80% with a feasible category. Normality tests showed that data from both small and large groups were normally distributed. The N-gain analysis indicated an average of 31.69 in the small group and 40.69 in the large group, both classified as moderately effective. In addition, students’ responses to the SNAMBO media reached 80%, categorized as very good. These findings demonstrate that SNAMBO media is attractive, easy to use, and beneficial in helping students understand LCM and GCD concepts. Furthermore, it provides an innovative alternative to game- based mathematics learning that enhances student engagement. Based on these results, SNAMBO is not only valid, feasible, and effective, but also strongly supports the mathematics learning process. Therefore, this media is highly necessary as an innovative tool to improve the quality of elementary school mathematics learning.